MEDIA SOSIAL SEBAGAI KONSTRUK PSIKOSOSIAL DAN STRATEGI PEMASARAN PADA PENJUAL TENUN BADUY - Tetty Rimenda; Tika Dwi Ariyanti; Rahma Nur Praptiwi; Iftita Rahmi (Taksasila Edukasi Insani, 2025)
The Baduy community, residing in the Kanekes mountainous region, is known for its strong adherence to customary traditions and resistance to modernization. However, technological developments have prompted some members, particularly those from the Outer Baduy group, to adopt the internet and utilize social media for marketing their woven products. This study examines social media not only as a marketing tool but also as a psychosocial construct that reflects changes in how the Baduy people interact and build trust within digital networks. The research aims to explore the use of social media and its related constructs in the marketing practices of Baduy tenun sellers in Kaduketug Village, Banten. The study focuses on three constructs: rating and review, recommendation and referral, and forum and community. A case study approach was employed, with data collected through in-depth interviews. The unit of analysis comprised 19 tenun sellers who use social media, of whom four were selected for intensive interviews. The findings reveal that WhatsApp and Facebook are the most frequently used platforms, followed by Instagram. The most dominant constructs applied were review and recommendation.Keywords: Marketing Strategy, Psychosocial Construct, Social Commerce, Social Media, Tenun Baduy